Is Optical Coherence Tomography a Useful Tool to Objectively Detect Actual Posterior Vitreous Adhesion Status? - Thomas Bertelmann; Christina Goos; Walter Sekundo; Stephan Schulze; Stefan Mennel (Case Reports in Ophthalmological Medicine)
Purpose. To objectively detect true posterior vitreous cortex (PVC) adhesion status using a commercially available swept-source OCT device (DRI OCT-1, Atlantis©). Material and Methods. Case report, review of the literature, and methodical discussion of concepts to improve OCT-guided PVC imaging. Results. Standard OCT imaging misdiagnosed PVC adhesion status as totally detached in this case report when using a horizontal 6 mm scan only. Contrariwise imaging the same eye with a 12 mm horizontal scan, partial posterior vitreous detachment (PVD) and the presence of a bursa premacularis were clearly discernible. Besides a broader scan, specific scan patterns, highest resolution, and contrast sensitivity, an anterior-to-posterior adjusted scan through the entire vitreous as well as the detection of characteristic undulating aftermovements might enhance the capability of OCT imaging to detect true PVC adhesion status. Conclusions. Further developments are needed to address these issues and to establish OCT recordings as the standard and objective method of choice in PVC adhesion status imaging.